Visualising care: representing decision models for conservation - Henderson, Jane; Lingle, Ashley (Journal of the Institute of Conservation, 2025)
This article critically examines the visual models that represent conservation decision-making, arguing for a shift from linear, exclusionary frameworks toward inclusive, reflexive and systems-based approaches. Traditional models, such as decision trees, flow diagrams and scoring matrices, offer structure and clarity, particularly for novice practitioners. However they can oversimplify complex realities, prioritising measurable outcomes and technical certainty over subjective, emotional and ethical dimensions. These models risk narrowing our perspectives on care by marginalising stakeholders, reinforcing hierarchies and excluding diverse perspectives, particularly in sensitive or contested heritage contexts. We use case studies and examples including the Hillsborough disaster archive to discuss how prioritising material preservation over access and social responsibility can result in profound failures of care. In such cases, the conservator's role must shift from control to facilitation, recognising that true care may lie in enabling others' engagement with heritage. To address the limitations of the dominant visual models for conservation decision-making, the article proposes a systems-thinking approach that embraces complexity, interconnectedness and change. The care that conservators offer is reframed as a dynamic, co-evolving practice shaped by relationships across time, space and disciplines. A double helix model is offered that visualises this interplay, integrating material and socio-cultural dimensions of care. This model supports adaptive, feedback-informed decision-making that aligns technical actions with cultural meaning and long-term sustainability. Our care should value plural perspectives, embrace uncertainty and reposition conservation as an enabling, collaborative practice. By reimagining how care decisions are described we can better reflect the lived realities of heritage and the communities it serves.